High fidelity computer generated forces (CGF) flight models - Teo, Yi Kiat. (2009)
This project is a continuation of the student’s work involvement on the preparation for the development of Computer Generated Forces (CGF) flight models for the F16 Flight Simulation System during Industrial Attachment (IA) with ST Electronics (Training & Simulation Systems) (STEE-T&S) Pte Ltd. CGF are virtual entities simulated by the computer software to inject realism into the simulated environment. CGF flight model validation is, thus, crucial to ensure good fidelity so that the CGF accurately represents the real-world aircraft for the intended use in pilot training. This report outlines the CGF flight model validation process, from the beginning of its preliminary design analysis to in-depth maneuver and performance checks. Preliminary flight performance analysis involves evaluating performance parameters based on the specification data used to define the flight model, and validating against actual flight test results obtained from flight manuals. Possible optimizations are identified, and tuning of the flight model is carried out until the performance parameters match the actual flight test results with sufficient accuracy. Subsequently, test cases are implemented for preliminary performance parameters validation by testing the flight model through various profiles automatically. In addition, maneuvers are validated through test-runs to ensure that the flight model is able to execute the different basic fighter maneuvers (BFM) correctly and accurately. The development of the flight simulation system is still ongoing, and this thesis described the latest results from the CGF flight model validation process.